Resolvin D1 blocks H(2)O(2)-mediated inhibitory crosstalk between SHP2 and PP2A and suppresses endothelial-monocyte interactions - Chattopadhyay, Rima (Free Radic Biol Med, 2018)
In recent years, various studies have demonstrated a role for endogenously derived specialized proresolving mediators such as resolvins in the resolution of inflammation. In exploring the signaling mechanisms, in the present study we show that Resolvin D1 (RvD1) reduces LPS-induced endothelial cell (EC)-monocyte interactions via blocking H(2)O(2)-mediated PP2A inactivation, NFκB activation and ICAM1 and VCAM1 expression. In addition, we found that H(2)O(2)-mediated SHP2 inhibition leads to tyrosine phosphorylation and inactivation of PP2A by LPS, which in turn, accounts for increased NFκB activation and ICAM1 and VCAM1 expression facilitating EC-monocyte interactions and all these LPS-mediated responses were reduced by RvD1. Furthermore, the suppression of NFκB activation, ICAM1 and VCAM1 expression and EC and monocyte interactions by RvD1 involved its receptors ALX/FPR2 and GPR32 as inhibition or neutralization of these receptors negated its effects. Besides, pertussis toxin completely prevented the effects of RvD1 on inhibition of LPS-induced H(2)O(2) production, SHP2 and PP2A inactivation, NFκB activation, ICAM1 and VCAM1 expression and EC and monocyte interactions. Together, these observations suggest that RvD1 via activation of Gi-coupled ALX/FPR2 and GPR32 receptors blocks LPS-induced H(2)O(2)-mediated SHP2 and PP2A inactivation, NFκB activation, ICAM1 and VCAM1 expression and EC-monocyte interactions, which could be one of the several possible mechanisms underlying the anti-inflammatory actions of this specialized proresolving mediator.